272 Evaluation of measures for the management of high-risk water sources in communities for child drowning prevention in Thailand. (1st September 2016) - Gerdmongkolgan, Suchada; Ekchaloemkiet, Som
Abstract : Background: In Thailand, drowning is the number one cause of death among children under 15 years of age, whose drowning death rate ranged from 7.6 to 11.5 per 100, 000 child population between 2004 and 2013. Objective: To evaluate the measures for the management of high-risk water sources in communities by installing warning signboards and easily available water safety devices for child drowning prevention. Methods: This evaluative research was conducted in two types of communities: one with the installation of warning signboards on water safety and advice for assisting drowning victims and making simple water safety devices that could be acquired in the community such as empty plastic 1-gallon containers, empty plastic water bottles, long sticks, and ropes, and the other without any water safety signboards or devices. Data were collected using a questionnaire and an interview form, and then analysed to determine percentages and standard deviations; and ANOVA was also performed. Results: The residents in the communities with the water safety measures for high-risk natural water settings by installing warning signboards had a higher average score on knowledge, understanding, and perception about drowning risks than that in the communities without such measures. However, the difference was not statistically significant. In the communities with such measures, 68.75% of the people realised that warning signboards were useful for child drowning prevention, while 87.07% regarded the water safety devices as useful for reducing drowning risk – the difference being significant, compared with that in the communities without such devices. Conclusion and discussion: The management of high-risk natural water settings undertaken by the community by installing warning or advice signboards and making available water safety devices made of locally available materials is regarded by community members as useful and effective in reducing child drowning risk.